ANALISIS PRAKTIK E-ACCOUNTING ENTITAS MIKRO, KECIL DAN MENENGAH DALAM MENGHADAPI SISTEM AKUNTANSI DAN TANTANGAN BISNIS DI ERA SOCIETY 5.0: Studi Kasus Pada Umkm Kabupaten Deli Serdang - Atikah, Sindi; Rizqy Fadhlina Putri (Jurnal Budgeting, 2024)
The purpose of this research is to determine whether Accounting Knowledge, Information Technology, Education Level, Work Motivation, Business Experience and Competition Level Influence E-Accounting Practices of Micro, Small, and Medium Entities in MSMEs in Deli Serdang Regency. The type of research conducted is quantitative research using primary data in the form of questionnaires. The population in this study were MSME actors in Deli Serdang Regency totaling 26,818. The sample used in this study used simple random sampling, namely 49 samples with several criteria. The data analysis method used is multiple linear regression and hypothesis testing using SPSS. The results of the study indicate that accounting knowledge of information technology, education level and business experience partially and significantly influence E-Accounting practices while work motivation and competition level partially and significantly do not influence E-Accounting practices. Accounting Knowledge, Information Technology, Education Level, Work Motivation, Business Experience and Competition Level simultaneously and significantly influence E-Accounting practices.